Uji efektivitas antidiabetes nanoherbal dan ekstrak etanol daun toppaspara (Mikania micrantha Kunth) Pada Tikus Putih Jantan (Rattus Norvegicus) yang diinduksi streptozotosin - Indah Setyarini, Putri Ayu; Gunawan , Muhammad; Safriana, Safriana; Fatimah , Cut (Journal of Pharmaceutical and Sciences, 2025)
Diabetes mellitus is a metabolic disease characterised by hyperglycemia caused by insufficient insulin production, insulin resistance, or both. The use of natural ingredients as a treatment option for diabetes mellitus can be developed as an alternative treatment, one of which is the toppaspara plant (Mikania micrantha Kunth.). The very small particle size in nano form is used to increase antidiabetic activity. Toppaspara leaves (Mikania micrantha Kunth.) have been empirically used as an antidiabetic, but this has not been scientifically proven. This research aims to determine the effectiveness of nanoherbal and ethanol extract of toppaspara leaves. This research was carried out experimentally, including the manufacture of simplicia, characterisation of simplicia, characterisation of nanoherbals and testing of antidiabetic effectiveness. Male white mice were induced with 2.5% streptozotocin intraperitoneally. Administration of 0.5% CMC suspension, nanoherbal and ethanol extract of toppaspara leaves at 50 mg/kgBB, 100 mg/kgBB, 200 mg/kgBB, metformin 45 mg/kgBB. The number of decreases in blood glucose levels is calculated; from the number of decreases in blood glucose levels, the percentage decrease in blood glucose levels is calculated. This analysis test uses One-way ANOVA followed by the Tukey test. The results of phytochemical screening of fresh leaves, simplicia ethanol extract and nano herbal toppaspara leaves contain secondary metabolite compounds such as alkaloids, tannins, flavonoids, saponins, steroids and glycosides. The results of the One Way ANOVA test and the Tukey test showed that nanoherbal 100 mg/kgBW and ethanol extract of toppaspara leaves 200 mg/kgBW were the best as antidiabetics and were not significantly different from metformin 45 mg/kgBW as a comparison.